2013
DOI: 10.1158/1541-7786.mcr-12-0113
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Long-Term Expansion and Self-Renewal Potential of Pediatric Acute Myeloid Leukemia–Initiating Cells By PTK787/ZK 222584

Abstract: Although most children with acute myeloid leukemia (AML) achieve complete remission, the relapse rate is 30% to 40%. Because it is thought that leukemia-initiating cells (LIC) are responsible for AML relapses, targeting these cells might improve outcome. Treatment of pediatric AML blasts with the receptor tyrosine kinase (RTK) inhibitor PTK787/ZK 222584 (PTK/ZK) induces cell death in vitro. However, the role of PTK/ZK inhibition on outgrowth of (pediatric) LICs is unknown. In this study, we cultured CD34þ cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this study we have found that VEGF111b itself reduced the VEGF-R2 tyrosine phosphorylation and accordingly downstream signaling, the phosphorylation of PI3K, Akt, and ERK1/2. Research has showed that VEGF-R2 tyrosine kinase inhibitors can reduce the phosphorylation of PI3K, Akt, and ERK1/2 [ 20 ]. In supplementary experiments, we added VEGF111b polyclonal antibody we prepared in the conditioned medium of SKOV3 cells overexpressing VEGF111b.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have found that VEGF111b itself reduced the VEGF-R2 tyrosine phosphorylation and accordingly downstream signaling, the phosphorylation of PI3K, Akt, and ERK1/2. Research has showed that VEGF-R2 tyrosine kinase inhibitors can reduce the phosphorylation of PI3K, Akt, and ERK1/2 [ 20 ]. In supplementary experiments, we added VEGF111b polyclonal antibody we prepared in the conditioned medium of SKOV3 cells overexpressing VEGF111b.…”
Section: Discussionmentioning
confidence: 99%
“…10B), suggesting its usefulness to help eradicate the most resistant cancer cells from the whole cell population. To this end, vatalanib has also been reported to impair the long term expansion and self-renewal potential of acute myeloid leukemia-initiating cells [32].…”
Section: Discussionmentioning
confidence: 99%